Strategi Humas Politeknik Kesehatan Palu Dalam Menarik Calon Mahasiswa Baru - Teuku Islamul Izulhaq; Sadiyah El Adawiyah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The aim of this research is to examine the Public Relations (PR) strategies within the Public Relations Department of the Ministry of Health Polytechnic (Poltekkes) Palu in attracting prospective new students. The study employs Ronald D. Smith's Strategic Planning for Public Relations, which categorizes its steps into four phases: formative research, strategy, tactics, and evaluative research. The research methodology used is a qualitative approach with a case study. Data is collected through observation and interviews with key informants from the Public Relations Department of Poltekkes Palu and relevant stakeholders. The findings from the formative research phase indicate that Poltekkes Palu's PR has identified several conventional strategies that are not effective in attracting new students, such as brochures, banners, and traditional forms of socialization. In the strategy phase, Poltekkes Palu plans to create podcasts to build brand awareness and market through social media as part of a broader marketing tactic. Social media is deemed a highly relevant channel, especially for reaching high school students. During the evaluation of the previous academic year, the Public Relations Department of Poltekkes Palu recognized valuable insights into the shortcomings of their strategies for student recruitment. The evaluation results show that the use of social media and digital marketing was not fully implemented in the previous academic year. Therefore, evaluative research serves as the foundation for identifying areas of improvement and refinement.